Anderson-Fabry disease cardiomyopathy: an update on epidemiology, diagnostic approach, management and monitoring strategies - Averbuch, Tauben; White, James A.; Fine, Nowell M. (Frontiers in Cardiovascular Medicine, 2023)
Anderson-Fabry disease (AFD) is an X-linked lysosomal storage disorder caused by deficient activity of the enzyme alpha-galactosidase. While AFD is recognized as a progressive multi-system disorder, infiltrative cardiomyopathy causing a number of cardiovascular manifestations is recognized as an important complication of this disease. AFD affects both men and women, although the clinical presentation typically varies by sex, with men presenting at a younger age with more neurologic and renal phenotype and women developing a later onset variant with more cardiovascular manifestations. AFD is an important cause of increased myocardial wall thickness, and advances in imaging, in particular cardiac magnetic resonance imaging and T1 mapping techniques, have improved the ability to identify this disease non-invasively. Diagnosis is confirmed by the presence of low alpha-galactosidase activity and identification of a mutation in the GLA gene. Enzyme replacement therapy remains the mainstay of disease modifying therapy, with two formulations currently approved. In addition, newer treatments such as oral chaperone therapy are now available for select patients, with a number of other investigational therapies in development. The availability of these therapies has significantly improved outcomes for AFD patients. Improved survival and the availability of multiple agents has presented new clinical dilemmas regarding disease monitoring and surveillance using clinical, imaging and laboratory biomarkers, in addition to improved approaches to managing cardiovascular risk factors and AFD complications. This review will provide an update on clinical recognition and diagnostic approaches including differentiation from other causes of increased ventricular wall thickness, in addition to modern strategies for management and follow-up.